Teaching the Holocaust : educational dimensions, principles and practice - Davies, Ian, 1957- (Continuum, 2000)
Offers a comprehensive treatment of Holocaust education, blending introductory material, broad perspectives and practical teaching case studies. This work shows how and why pupils should learn about the Holocaust.